2019
DOI: 10.1080/10903127.2019.1636912
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Different Hair and Skin Decontamination Strategies with Identification of Associated Hazards to First Responders

Abstract: Prompt disrobing and minimization of time to casualty decontamination are key to the effective treatment of individuals exposed to toxic chemicals. Established procedures for mass casualty decontamination that involve the deployment of equipment for showering with water (such as the ladder pipe system [LPS] and technical decontamination) necessarily introduce a short, but critical delay. The purpose of this study was to investigate the effectiveness of dry and wet decontamination approaches (individually and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Results from both MeS quantitation and UV imaging demonstrated that there was less simulant remaining on the skin following each of the improvised decontamination protocols compared to no-decontamination control, consistent with previous in vitro and human volunteer studies [ 3 – 7 ]. In addition, more simulant was removed from the skin when both improvised dry and wet decontamination were conducted in sequence compared to individually.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Results from both MeS quantitation and UV imaging demonstrated that there was less simulant remaining on the skin following each of the improvised decontamination protocols compared to no-decontamination control, consistent with previous in vitro and human volunteer studies [ 3 – 7 ]. In addition, more simulant was removed from the skin when both improvised dry and wet decontamination were conducted in sequence compared to individually.…”
Section: Discussionsupporting
confidence: 85%
“…Whilst decontamination of skin using IOR methods has been subjected to controlled efficacy testing in vitro [ 3 , 4 ] little is known of the efficacy of these individual decontamination procedures when conducted in sequence. Although human volunteer studies have investigated the effectiveness of dry decontamination [ 5 – 7 ], improvised wet decontamination has yet to be investigated. Further, as mass decontamination strategies rely on implementation in series of dry followed by wet decontamination protocols as new resources become available at the scene of the incident, it is reasonable to explore the potential beneficial effects of sequential improvised dry and wet decontamination protocols, before these resources arrive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In a previous study, it was shown that the textile material was able to absorb a non-particulate test substance together with sebum from the skin surface. 25 It was hypothesized that a skin decontamination from particulate substances might be more challenging as the skin surface is not homogeneous but characterized by the presence of wrinkles, furrows, follicular orifices, and sweat glands, which serve as an appropriated reservoir for topically applied particulate substances. 26 Therefore, a viscous fluid will be applied to the skin, which extracts these particulate substances from the structures of the skin surface, allowing a facilitated removal by the highly absorbent textile material afterward.…”
Section: Introductionmentioning
confidence: 99%
“…For non‐particulate substances, it could already be shown that highly absorbent textile materials are well suited to efficiently remove substances from the skin23 by pressing them gently onto the skin without rubbing in order not to influence the integrity of the stratum corneum24 or to accelerate follicular penetration 18. In a previous study, it was shown that the textile material was able to absorb a non‐particulate test substance together with sebum from the skin surface 25…”
Section: Introductionmentioning
confidence: 99%